An inherent fault current blocking modular series multilevel converter using half-bridge sub-modules for grid integration - Sukrashis Sarkar; Abhrodip Chaudhury; Anandarup Das (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper proposes an inherent fault current blocking modular series multilevel converter (MSMC) using half-bridge (HB) sub-modules (SMs) for grid integration. The proposed converter uses passive filters to decouple the AC and DC side. Compared to conventional three-phase modular multilevel converters (MMCs) that use half-bridge sub-modules (HBSMs), the new MSMC design significantly reduces the number of switching devices required. Furthermore, one of the features of the proposed MSMC is its inherent ability to limit fault currents, which is achieved through its unique topological configuration whereas the conventional HB-MMC is susceptible to DC and AC faults. Despite these advancements, the new MSMC design retains all the desirable characteristics of conventional HB-MMCs, ensuring compatibility and ease of adoption. The paper thoroughly examines the operation of the MSMC under both steady-state and fault conditions. It also discusses the equivalent voltage decoupling circuit, energy balancing which is essential for the proper functioning of the converter. Additionally, the pre-charging process of the sub-module capacitors, a critical step for ensuring the safe start-up of the converter, is discussed in detail. Furthermore, Extended topologies can be derived from proposed topology for different applications.